TAZKIYYAT AL-NAFS, DHIKR, AND SENSITIVITY AS CULTURAL MODEL OF INDONESIAN COMMUNITIES IN FACING COVID-19 PANDEMIC - Halim Purnomo; Firman Mansir; Tumin Tumin; Caswito Caswito; Septi Gumiandari; Maulana Mualim (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2020)
This article used a qualitative method with the approach of study- ing literature in the fields of religious psychology, Islamic psychology, and culture to obtain concepts and theories that are relevant to studies on facing the anxiety and worries caused by the outbreak of COVID-19. The results reveal the COVID-19 outbreak has various impacts on Indo- nesian people, they are encouraged to express optimism, psychological sensitivity, and social piety through various empathical (caring) ways as the implementation of the theology of al-Ma’un. And through tazkiyyatu al-Nafs and dhikr as models to eliminate anxiety and worries caused by COVID-19. Media reporting about COVID-19, besides being informa- tive, also causes anxiety so that sensitivity and social piety of the com- munity are needed. This article explained that through the rites of tazkiyyatu al-Nafs, dhikr, and implementation of al-Ma’un theology de- veloped by KH. Ahmad Dahlan, as well as a collaboration of cultural approaches with the psychology of religion, can reduce the level of anxi- ety, worry, and fear of the people caused by COVID-19.